APLIKASI GAME WIN START LA BERBASIS ANDROID - Roiduddin Al Adib; Nurul Fuad; Retno Wardhani (Universitas Islam Lamongan, 2017)
Game is one of the entertainment that is fun and interesting way to spend leisure time or relieve boredom at the time of waiting, a variety of games or game has been created and produced many free or paid. Starting from a brain teaser game theme, sports, to adventure. An android based games can provide entertainment for players. The purpose of this study was to design and build a game that can be played in your spare time and eliminate boredom when waiting. The method used in designing and building this game is the method of